Controllable assembly, characterization and catalytic properties of a new Strandberg-type organophosphotungstate. Issue 4 (22nd December 2015) - Ma, Hong-Xin; Du, Jing; Zhu, Zai-Ming; Lu, Ting; Su, Fang; Zhang, Lan-Cui
Abstract : A new Strandberg-type organophosphotungstate was assembled under hydrothermal conditions and displayed good fluorescence properties and catalytic activity. Abstract : Using phenylphosphonic acid, simple tungstate and copper(ii ) compounds as starting materials, an organic–inorganic hybrid Strandberg-type organophosphotungstate, {[(Cu(H2 O)(μ-bipy))2 (C6 H5 PO3 )2 W5 O15 ]} n (bipy = 4, 4′-bipyridyl) (1 ), was assembled successfully under hydrothermal conditions and characterized by physico-chemical and spectroscopic methods. Compound1 represents the first example of a transition metal complex modified organophosphotungstate cluster. In the crystal structure of compound1, the polymeric 1-D Cu-bipy n chains are interconnected by [(C6 H5 PO3 )2 W5 O15 ] 4− (abbreviated as {(C6 H5 P)2 W5 }) units into a 3-D framework. A hollow Keggin isopolytungstate [H2 W12 O40 ] 6− (W12 )-Cu(ii ) coordination polymer, {[Cu(bipy)2 ((μ-bipy)Cu(bipy))2 (H2 W12 O40 )]·12H2 O} n (2 ), was obtained at different molar ratios of the starting materials and pH. The two Cu(ii ) coordination polymers exhibit good acid-catalytic activity for the synthesis of cyclohexanone ethylene ketal. Their fluorescence properties were studied.